Factors Affecting Patients' Repeat Visits To The Executive Polyclinic At The Prof. Hospital. dr. R.D Kandou Manado - Reyne Miehelty Salindeho; Eva Mariane Mantjoro; Theresia M.D. Kaunang (International Publisher, 2023)
The rapid development of science and technology, as well as the increasingly high level of public education, is a challenge for hospitals in providing quality health services. Interest in repeat visits is a behavior that appears in response to objects that indicate a customer's desire to make a repurchase. Consumer satisfaction is determined by consumer perceptions of product or service performance in meeting consumer expectations. Consumers are satisfied if their expectations are met or will be very satisfied if customer expectations are exceeded. Patient satisfaction will be fulfilled if the process of delivering health services to consumers is in accordance with what is perceived by the patient. Outpatient health services are the backbone of the health service system. The purpose of this research is to find out the factors that influence patient repeat visits to the health service system. The purpose of this research is to find out the factors that influence patient repeat visits to the executive polyclinic of Hospital RSUP Prof. Dr. R.D. Kandou Manado. This study used a quantitative method, using an analytic survey research type with a cross sectional approach. Data obtained by using a questionnaire. The population is all patients who visit the executive polyclinic more than once. Sampling using purposive sampling technique totaling 228 outpatients. Data analysis performed was univariate, bivariate and multivariate, and categorical data using statistical analysis with the Chi-Square test was significant if p <0.05 and multivariate with logistic regression. The results showed that there was a relationship between the variables of infrastructure, speed and ease of service and personal service with factors that influenced repeat visits, while for the location variable there was no significant relationship. The speed and ease of service factors are most related to the factors that influence repeat visits. At the Executive Polyclinic of Prof. RSUP. Dr. R.D. Kandou Manado.